2000
DOI: 10.1590/s0301-80592000000200015
|View full text |Cite
|
Sign up to set email alerts
|

Componentes químicos associados à resistência de Lycopersicon hirsutum f. typicum a Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae)

Abstract: Este trabalho foi conduzido em casa de vegetação no Campus da Universidade Federal de Viçosa, Minas Gerais, Brasil de maio a setembro de 1997 e objetivou estudar a resistência do acesso LA 1777 de Lycopersicon hirsutum f. typicum a Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) e os prováveis compostos químicos envolvidos na resistência. Utilizaram-se as cultivares de Santa Clara (tomate para consumo in natura) e IPA-5 (tomate industrial) de Lycopersicon esculentum como padrões de suscetibilidade à praga. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…This significance indicates the existence of genetic variability among the tested genitors, a fact of importance in determining the estimates of the genetic control of these traits. Considering this, there are many studies reporting the effect of zingiberene on oviposition, preference and even the survival of arthropod pests (Ecole, Picanço, Moreira, & Magalhães, 2000;Maluf et al, 2001;Azevedo, Faria, Maluf, Oliveira, & Freitas, 2003;Gonçalves et al, 2006;Silva et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…This significance indicates the existence of genetic variability among the tested genitors, a fact of importance in determining the estimates of the genetic control of these traits. Considering this, there are many studies reporting the effect of zingiberene on oviposition, preference and even the survival of arthropod pests (Ecole, Picanço, Moreira, & Magalhães, 2000;Maluf et al, 2001;Azevedo, Faria, Maluf, Oliveira, & Freitas, 2003;Gonçalves et al, 2006;Silva et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…However, due to its concealed habit, it requires several treatments per growing season, which in turn can result in a decrease of efficacy by the development of insecticide resistance by this pest (Ecole et al 2000, Siqueira et al 2000, Lietti et al 2005, Strassera 2009). In the search for other pest management practices, biological control is a reliable alternative to be considered (Altieri & Nichollls 1999, van Lenteren & Manzaroli 2000.…”
mentioning
confidence: 99%
“…We found higher density of eggs on Dehghan and Falat 3 but larva density in these genotypes was lower than egg density which lower number of larvae may reflect higher mortality of T. absoluta during leaf mesophyll feeding (Suinaga et al 1999(Suinaga et al , 2004aEcole et al 2000Ecole et al , 2001. King Ston and Early Urbana showed the lowest larvae density while these genotypes had higher oviposition rate than larvae density that it may be due to lethal effects of glandular trichom.…”
Section: Discussionmentioning
confidence: 68%
“…TLM population density of larvae varied largely in the current no choice assay among the genotypes and these variations should be strictly related to the plant features, reflecting differences either in nutrients required by the pest or in secondary compounds, taking in count that all cultivars were cultivated under the same environmental conditions. Previous studies demonstrated that quantity and quality of the food sources influence fitness (survival rates, developmental duration, egg laying and other parameters) of moth (Gonçalves et al 1998;Leite et al 1999Leite et al , 2001Ecole et al 2000Ecole et al , 2001Suinaga et al 2004;Oliveira et al 2009;).…”
Section: Discussionmentioning
confidence: 99%